Study of various curved-blade impeller geometries on power consumption in stirred vessel using response surface methodology - Afshar Ghotli, R.; Abdul Raman, Abdul Aziz; Ibrahim, Shaliza; Baroutian, Saeid; Arami-Niya, A. (Elsevier, 2013)
The geometry of an impeller is a determining factor in power demand, which in turn determines the cost of mixing operation in stirred tanks. In this work, the power requirements for seven types of 6-curved blade impellers of varying curvature angles and central disk sizes, were analyzed via response surface methodology (RSM) and compared to a Ruston turbine. The experiments were conducted using water as the working fluid in a standard mixing vessel. Power consumptions were measured using a load cell arrangement for a wide range of speeds in both aerated and un-aerated conditions. The data revealed that the power number (NP) of the elliptical shape curved blade was 2.8 whereas for CB180°, CB160° and CB140° were respectively 21, 32 and 75 higher. Furthermore, the power number values for the impeller with a 3/4D central disk size was approximate 3.4, while the impellers with 1/2, 1/4 and without central disk were respectively 15, 20 and 23.5 higher. The results under different gas flow rates illustrated the power reduction of the curved blades impellers, both various central disk sizes and curvature angles, were in the range of 1-20 meanwhile the Rushton turbine was in the range of 5-45. Curvature angle and central disk size found as the significant parameters through variance analysis (ANOVA). The results also indicated that the significance of the central disk size was less than the other variables. The R-squared values indicated a fitting of the models with the experimental data. In conclusion, the curved blade impellers were found to have lower power consumption in both aerated and un-aerated conditions in comparison with the Rushton turbine. © 2012 Taiwan Institute of Chemical Engineers.